Lipid Profile in New and Recurrent Ischemic Stroke Patients at Haji General Hospital of North Sumatra Indonesia - Andina, Meizly; Pratiwi, Lisa Nabila; Aribowo, Fadhilah Ramadhan (International Journal of Human and Health Sciences (IJHHS), 2019)
Introduction: Stroke refers to any sudden neurological disorder that occurs due to the cessation of blood flow through the arterial supply system of the brain. The etiology obstructions are atherosclerosis. There was an imbalance of lipid profiles in patients with ischemic stroke There was an imbalance of lipid profiles in patients with ischemic stroke. The objective of this research is to determine differences between lipid profile in new ischemic stroke patients with recurrent stroke at Haji General Hospital of North Sumatra Indonesia in 2015-2016. Methods: This is a cross-sectional study using total sampling method with a total of 64samples. Secondary data obtained from General hospital Haji Medan. Secondary data collected were data on lipid profile in patients with acute stroke and recurrent stroke by collecting medical records. Results: The result from the acute stroke patients found HDL levels of 33.97 mg/dl, recurrent stroke patients found HDL levels of 35.25 mg/dl. LDL levels in acute stroke patients were 109.56 mg/dl and recurrent stroke patients were 123.16 mg/dl. In new ischemic stroke patient, the average value of triglyceride levels was 143 mg/dl and the average value of total cholesterol was 205.8 mg/ dl. In recurrent ischemic stroke patient, the average value of triglyceride levels was 165.2 mg/dl and the mean total cholesterol level was 180.8 mg/dl. Discussion: There are no differences of lipid profile in new and recurrent ischemic stroke patients at Haji General Hospital of North Sumatra Indonesia in 2015-2016 (p>0.05) International Journal of Human and Health Sciences Vol. 03 No. 03 July’19. Page: 146-149